Peredaran Obat Terlarang Di Indonesia dan Upaya Pencegahannya Oleh Badan Pengawas Obat Dan Makanan (BPOM) - Maria Teresa Wensen; Sari Mandiana; Agustin Widjiastuti (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Health is a human right and is an element of welfare because health is a community need and must be realized. One of the health supports is medicine, the function of medicine is prevention, healing, recovery, health improvement, and contraception, for humans. Based on its function and the dangerous consequences of drug consumption, its manufacture and distribution must be under the supervision of the Food and Drug Monitoring Agency, by Presidential Regulation Number 80 of 2017 concerning the Food and Drug Monitoring Agency.Under his supe rvision, illegal drugs remain widespread and consumed in inappropriate doses by the public, including hard drugs and narcotics. As a result of dependence, many drug traffickers are caught and repeat the same actions (recidivists). Drug recidivism is regulated in Law Number 5 of 2009 concerning Narcotics Article 144 paragraph (1). However, the distribution of narcotics continues to occur. From the results of this research, the author found that BPOM's efforts as a supervisory body need to be increased, not only collaborating between agencies but also inviting the community, this is also to realize Chapter XIII concerning Community Participation, Law Number 35 of 2009 concerning Narcotics. Also, apply the most severe sanctions to create a deterrent effect so that there is no repetition of criminal acts of narcotics trafficking.